Marginalized Voices: Homeless Media as an Agent of Social Transformation - Nur Azizah; Bambang Mudjiyanto; Hayu Lusianawati; Launa (JURNAL ILMIAH NUSANTARA, 2026)
Today the shifting media platform usage from conventional media accounts to homeless media (HM) is an undeniable fact. Through qualitative research using a phenomenological and virtual ethnographic approach, as well as utility and satisfaction theory, this study found that HM accounts have been widely operating on various official social media platforms, filling the information gap that conventional media cannot reach, especially at the level of marginalized and local communities. Despite internal challenges still surrounding HM, it holds significant potential as an alternative information provider, especially for local and marginalized communities. HM is a crucial phenomenon in the social transformation of Indonesia's digital society landscape today. With its speed of distribution, content innovation, and social mobilization capabilities, HM opens new avenues for information democratization, public participation, and social change dynamics. Synergy between HM, conventional media, and the public, along with news content accuracy, ethics, and journalistic responsibility, will be key to achieving inclusive and meaningful social transformation in the future.